Patient Satisfaction Survey: Qualitative Evaluation Tool for Health Care Services - Agrawal, Tripti; Dutta, Amitava (Indian Journal of Community Health, 2025)
Background: A paradigm shift has been noticed by employing patient satisfaction survey as a tool for improvement of quality of patient care services in the hospital and more recently the same has been utilized as a market-driven approach to enhance the overall organizational performance of various health care establishments across the countries all over the world. Present study is aimed to study the satisfaction level of patients, various factors associated with such satisfactory outcome as well as to examine the root causes of dissatisfaction among patients availing the health care services. This in turn will enable us to improve the quality of health care delivery services in a tertiary care health facility owned by the government in Northern India. Material & Methods: Data was captured from admitted patients as well as from the clientele visiting various OPDs of the hospital with necessary randomization & with the aid of utilizing patient’s satisfaction survey questionnaire in the time period from July to the month of December of the year of 2023. A total of 102 patients visiting the hospital for OPD services or for admission were included in the present study. Analysis of the study findings were done using SPSS software version 20. Results: A total of 37 patients visiting various OPDs were interviewed and various parameters were captured using the questionnaire survey feedback forms. It was found that mean score of overall satisfaction rate of visitors of hospital was 4.6 as found by the users towards satisfaction score of communication by doctors. Mean score towards hospital cleanliness, amenities of waiting area, availability of prescribed medicines, waiting period in registration desk and behavior of hospital staffs were also found to be above ‘Very Good’ ratings. Conclusion: Good practices towards patient satisfaction are needed to be adhered on long run to ensure the delivery of quality health care to clientele.